Conductive binder, silicon-based negative electrode, and lithium-ion battery
Patent Information
- Application Number
- CN202611258435.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-30
AI Technical Summary
一些现有技术(如发明专利CN120829740B)介绍了通过加入交联剂引发聚合物形成静态的三维网状结构,该方法能够改善硅负极的结构稳定性,提高循环寿命,但这类静态网络在长循环的剧烈膨胀收缩中容易发生应力集中而不可逆断裂,提升幅度有限
[0037]倍率性能极其优异。 本发明通过充放电循环诱导仿生添加剂(如咖啡酸)发生电化学,并协同多糖类物质(如卡拉胶)在极片表面衍生出富硫固体电解质界面(SEI)膜。这一动态仿生双效网络构筑了坚固且连续的快速离子传输通道,显著降低了界面的电荷转移阻抗,极大地增强了锂离子在硅基负极材料中的反应动力学,从而大幅提升了锂离子电池的高倍率充放电性能。实验表明,采用本发明所述复合粘结剂制备的纯硅负极,在2C的大电流密度下具有1613.2 mAh g-1的可逆比容量。
Smart Images

Figure CN123004331A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of lithium-ion battery technology, specifically to a conductive binder, a silicon-based anode, and a lithium-ion battery. Background Technology
[0002] Lithium-ion batteries are highly efficient energy storage devices that have been widely used in recent years and have great development potential. Silicon-based materials, due to their extremely high theoretical specific capacity (up to 4200 mAh g⁻¹), are particularly promising. -1 Silicon, with its low lithium insertion / extraction potential, is considered one of the most promising next-generation lithium-ion battery anode materials for commercial applications and has received widespread attention. However, silicon undergoes a huge volume expansion (approximately 300%) during charging and discharging, and the enormous mechanical stress leads to silicon particle pulverization, electrode peeling, and rapid capacity decay, severely restricting its commercialization process.
[0003] Polymer binders not only play a crucial role in maintaining the integrity of the electrode structure but are also key auxiliary materials for preparing high-performance silicon anodes. Currently, the main methods to buffer the volume expansion of the electrode are the development of aqueous polymers rich in polar functional groups (such as polyacrylic acid and carboxymethyl cellulose) or the construction of three-dimensional cross-linked networks. Some existing technologies (such as invention patent CN120829740B) introduce the formation of a static three-dimensional network structure by adding a cross-linking agent to induce the polymer. This method can improve the structural stability of silicon anodes and increase cycle life. However, such static networks are prone to stress concentration and irreversible fracture during the drastic expansion and contraction of long cycles, resulting in limited improvement. At the same time, the drastic volume change of silicon anodes leads to the continuous rupture and reconstruction of the solid electrolyte interphase (SEI) film on its surface. This process continuously consumes active lithium and electrolyte, causing the SEI film to thicken continuously. This significantly reduces the electronic and ionic conductivity at the electrode interface, resulting in poor rate performance as an electrode material. The continuous side reactions and the sharp increase in interfacial impedance also lead to more polarization, resulting in a significant reduction in the fast-charging performance and initial coulombic efficiency of silicon-based anodes.
[0004] Currently, there is limited research on the dynamic evolution and active regulation of the inorganic composition and interfacial kinetics of the SEI film through binders during electrochemical cycling. Given this, there is an urgent need to develop a silicon-based anode fabrication method that is process-compatible, low-cost, and capable of significantly improving ion transport kinetics and rate performance by constructing a dynamic network and generating a robust SEI film. This would meet the demands of future large-scale energy storage and new energy vehicle systems for high-power, fast-charging lithium-ion batteries. Summary of the Invention
[0005] In view of this, the purpose of this invention is to at least partially solve one of the technical problems in the related art. This invention provides a conductive binder, a silicon-based anode, and a lithium-ion battery. The method is simple, environmentally friendly, and the prepared electrode can induce in-situ cross-linking polymerization of biomimetic additives during electrochemical cycling, and synergistically generate a functional solid electrolyte interphase (SEI) film with polysaccharides, constructing a dynamic dual-effect network with high mechanical strength and fast ion transport channels. This alleviates the problems of severe volume expansion, repeated SEI film rupture, and slow interfacial ion transport kinetics in silicon-based anodes during charge and discharge, improving the electrochemical performance of the electrode, including structural stability, initial coulombic efficiency, rate performance, and cycle performance.
[0006] To solve the above-mentioned technical problems, the present invention is implemented as follows:
[0007] In a first aspect, the present invention provides a conductive binder comprising a polymer, a polysaccharide, and a biomimetic additive. When the conductive binder is used on a silicon-based negative electrode, during charge-discharge cycles, the biomimetic additive undergoes in-situ electrochemical polymerization and, in conjunction with the polysaccharide, derives and forms a functional solid electrolyte interface film on the surface of the silicon-based negative electrode.
[0008] In one embodiment, the biomimetic additive contains carbon-carbon double bonds and / or phenolic hydroxyl groups.
[0009] In one embodiment, the biomimetic additive includes one or more of tannic acid, phytic acid, gallic acid, caffeic acid, dopamine, chlorogenic acid, ferulic acid, catechin, and catechol.
[0010] In one embodiment, the biomimetic additive is caffeic acid and / or gallic acid.
[0011] In one embodiment, the polysaccharide is a sulfur-containing polysaccharide and / or a carboxyl-containing polysaccharide.
[0012] In one embodiment, the sulfur-containing polysaccharide includes carrageenan, heparin, chondroitin sulfate, fucosylated chondroitin sulfate, dermatan sulfate, and chemically modified sulfur-containing polysaccharides.
[0013] In one embodiment, the chemically modified sulfur-containing polysaccharide refers to a natural sulfur-free polysaccharide that has been sulfated to introduce a sulfate ester group.
[0014] In one embodiment, the carboxyl-containing polysaccharide includes one or more of the following: sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, sodium alginate, sodium hyaluronate, xanthan gum, guar gum, locust bean gum, konjac glucomannan, gum arabic, pectin, tamarind gum, pullulan, carboxymethyl chitosan, and cross-linked starch.
[0015] In one embodiment, the polysaccharide is carrageenan.
[0016] In one embodiment, the polymer is obtained by free radical polymerization of monomers, wherein the monomers include one or more of acrylic acid, methacrylic acid, lithium acrylate, sodium acrylate, vinyl alcohol, ethylene glycol, acrylamide, and methacrylamide.
[0017] In one embodiment, the polymer is polyacrylamide and / or polyacrylic acid.
[0018] Secondly, the present invention also provides a method for preparing the above-mentioned conductive adhesive, comprising the following steps:
[0019] (1) Add polysaccharide substances to the polymer solution and mix to obtain a polymer-polysaccharide composite solution;
[0020] (2) Add biomimetic additives to the polymer-polysaccharide composite solution and mix to obtain the conductive binder.
[0021] In one embodiment, step S1 is included before step (1): dissolving the monomer in a solvent and carrying out a polymerization reaction under the action of an initiator to obtain a polymer solution;
[0022] In one embodiment, the initiator includes one or more of potassium persulfate, sodium persulfate, ammonium persulfate, azobisisobutyronitrile, cerium sulfate, and cerium ammonium nitrate;
[0023] In one embodiment, the mass ratio of the monomer to the initiator is (10-50):1;
[0024] In one embodiment, the polymerization reaction is carried out at a temperature of 55-95°C and for a duration of 10-120 min.
[0025] In one embodiment, the solvent includes one or more of water, ethanol, ethylene glycol, n-propanol, isopropanol, and N-methyl-2-pyrrolidone.
[0026] In one embodiment, in step (1), the mass ratio of the polysaccharide to the monomer is 1~2:1~4.
[0027] In one embodiment, the mixing temperature is 60-90°C; the mixing time is 3-60 min.
[0028] In one embodiment, in step (2), the amount of the biomimetic additive added is 5-15% of the total mass of the solute.
[0029] Thirdly, the present invention also provides a silicon-based negative electrode sheet, the silicon-based negative electrode sheet comprising a current collector and a negative electrode coating disposed on the surface of the current collector, the negative electrode coating comprising a silicon-based active material, a conductive agent, and a conductive binder as described in the first aspect or a conductive binder prepared by the preparation method described in the second aspect.
[0030] In one embodiment, the mass ratio of the silicon-based active material, the conductive agent, and the conductive binder is (5-7):(1-3):(1-3).
[0031] In one embodiment, the silicon-based active material includes one or more of nano-silicon, micron-silicon, porous silicon, silicon-carbon composite, and silicon oxide.
[0032] In one embodiment, the conductive agent includes one or more of conductive carbon black, carbon nanotubes, graphene, and Ketjen black.
[0033] Fourthly, the present invention also provides a lithium-ion battery, the lithium-ion battery comprising the silicon-based negative electrode sheet described in the third aspect;
[0034] The lithium-ion battery has a discharge specific capacity of not less than 1200 mAh g at a 2C rate. -1 ;
[0035] In one embodiment, the capacity retention rate of the lithium-ion battery after 200 cycles at 1C rate is not less than 50%.
[0036] Implementing the technical solution of the present invention has at least the following beneficial effects:
[0037] The rate performance is exceptionally excellent. This invention induces electrochemical reactions in biomimetic additives (such as caffeic acid) through charge-discharge cycles, and synergistically, polysaccharides (such as carrageenan) derive a sulfur-rich solid electrolyte interphase (SEI) film on the electrode surface. This dynamic biomimetic dual-effect network constructs a robust and continuous fast ion transport channel, significantly reducing the charge transfer impedance at the interface and greatly enhancing the reaction kinetics of lithium ions in silicon-based anode materials, thereby significantly improving the high-rate charge-discharge performance of lithium-ion batteries. Experiments show that the pure silicon anode prepared using the composite binder described in this invention exhibits a rate performance of 1613.2 mAh g⁻¹ at a high current density of 2C. -1 The reversible specific capacity.
[0038] It exhibits high initial coulombic efficiency and good structural stability. Compared to existing static binder networks prone to stress concentration fracture, the biomimetic polymer network generated in situ in this invention can form strong multiple hydrogen bonds and chemical anchoring with the silicon particle surface, effectively buffering the huge volume expansion (approximately 300%) of silicon during lithium insertion / extraction. The robust derived SEI film avoids repeated exposure to new interfaces, reducing irreversible electrolyte decomposition and continuous consumption of active lithium, significantly improving the initial coulombic efficiency and long cycle life of the silicon anode. Its initial coulombic efficiency can reach 92%, and the capacity retention rate reaches over 60% after 200 cycles at 1C.
[0039] This invention offers both economic benefits and environmental friendliness. The polysaccharides and biomimetic additives used in this invention are widely found in nature, making the raw materials green, environmentally friendly, and inexpensive. The slurry preparation process is simple to operate, fully compatible with existing commercial lithium-ion battery electrode preparation processes, requires no expensive special equipment, and has extremely high industrialization potential.
[0040] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description
[0041] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0042] Figure 1 Infrared spectra of the adhesives prepared in Comparative Examples 1, 3, 5 and Example 2.
[0043] Figure 2 Images showing the nanoindentation results of the adhesives prepared in Comparative Examples 5, 7 and Example 2.
[0044] Figure 3 Peel strength curves of nano-silicon anode sheets corresponding to the binders prepared in Comparative Example 5 and Example 2.
[0045] Figure 4 The first-week constant current charge-discharge curves of the nano-silicon anodes corresponding to the binders prepared in Comparative Examples 5, 7, 2, and 3 are shown.
[0046] Figure 5 Rate performance of the nano-silicon anodes corresponding to the binders prepared in Comparative Examples 5, 7 and Example 2 at different current densities.
[0047] Figure 6 Example 2: Cyclic performance of the nano-silicon anode corresponding to the binder prepared in Example 2 at a current density of 1C.
[0048] Figure 7SEM images of the cross-sections of the nano-silicon anodes corresponding to the binders prepared in Comparative Examples 5, 7 and Example 2 before and after cycling.
[0049] Figure 8 SEM images of the nano-silicon anodes corresponding to the binders prepared in Comparative Examples 5, 7 and Example 2 before and after cycling.
[0050] The accompanying drawings have illustrated specific embodiments of the invention, which will be described in more detail below. These drawings and descriptions are not intended to limit the scope of the invention in any way, but rather to illustrate the concept of the invention to those skilled in the art through reference to particular embodiments. Detailed Implementation
[0051] The present application will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.
[0052] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges or individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0053] In the description of this application, "A and / or B" can include any of the cases of A alone, B alone, or A and B, where A and B are merely examples and can be any technical feature connected by "and / or" in this application.
[0054] Unless otherwise specified, the terms "comprising" and "including" as used in this invention can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0055] Unless otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form new technical solutions.
[0056] Unless otherwise specified, all technical features and optional technical features of this invention can be combined to form new technical solutions.
[0057] Unless otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order; for example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0058] This paper addresses a series of serious problems caused by the dramatic volume expansion (approximately 300%) of silicon particles during the charging and discharging process of silicon-based anodes in lithium-ion batteries. These problems include electrode material pulverization, electrode structure collapse, repeated rupture and regeneration of the solid electrolyte interphase (SEI) film, and the resulting continuous consumption of active lithium and electrolyte, a sharp increase in interfacial impedance, and significant degradation of rate performance and cycle life. The fundamental contradiction lies in the severe mismatch between the enormous mechanical stress of the silicon-based anode during lithium insertion / extraction and the limited buffering capacity of conventional binder systems. Furthermore, traditional SEI films, lacking self-repair capabilities, struggle to maintain interfacial stability during dynamic expansion and contraction, leading to rapid battery performance degradation and severely hindering the commercial application of silicon-based anodes.
[0059] The inventors re-examined the failure mechanism of silicon-based anodes—traditional research generally treats silicon expansion as a mechanical problem, with solutions focusing on improving the rigidity or static crosslinking degree of the binder. However, through analysis, the inventors discovered that even the optimal static crosslinking network (such as CN120829740B) still experiences irreversible fracture after long-term cycling. This indicates an inherent flaw in the rigid constraint strategy: the alternating stress generated by the repeated expansion and contraction of silicon cannot be effectively dissipated through fixed crosslinking points, and the stress eventually accumulates at weak points, leading to network collapse. More importantly, the inventors noted that the repeated rupture of the SEI film is not simply physical damage, but a chain reaction of failures at the chemical level—each rupture exposes a fresh silicon surface, triggering continuous electrolyte decomposition and interfacial impedance accumulation. These two types of failures (mechanical network fracture + interfacial chemical degradation) are coupled and mutually causal. Based on this, the inventors established the core innovation direction: transforming static passive resistance into dynamic active adaptation, while simultaneously considering the dual functions of network mechanical buffering and interfacial chemical regulation.
[0060] Based on this, the inventors proposed a novel dynamic biomimetic dual-effect network design concept: instead of relying on the traditional static cross-linking single physical buffer mechanism, it utilizes the electrochemical field driven during the charge-discharge cycle to induce the in-situ electrochemical polymerization of biomimetic additives containing carbon-carbon double bonds inside the electrode, forming an adaptive chemical cross-linking network that can be dynamically reconfigured with volume changes; at the same time, it uses polysaccharides to synergistically construct a dynamic dual-effect network that combines high mechanical strength and fast ion transport channels. Among them, the biomimetic additives possess both phenolic hydroxyl anchoring groups and polymerizable double bonds, enabling them to form multiple hydrogen bonds for strong anchoring with silicon particles while simultaneously forming dynamic cross-linking points under electrochemical drive. Polysaccharides are rich in polar functional groups (hydroxyl, carboxyl, or sulfate ester groups, etc.), which can form dense intermolecular hydrogen bonds with polymer backbones (such as polyacrylamide) to jointly construct a three-dimensional physical cross-linking network, providing basic mechanical support and adhesion for silicon-based anodes. At the same time, these polar groups can also form multi-point hydrogen bond anchoring with the oxide layer (Si-OH) on the surface of silicon particles and the current collector, enhancing the bonding strength between the active material layer and the current collector, and preventing particle shedding and electrode cracking during silicon volume expansion.
[0061] Specifically, the present invention adopts the following technical solution:
[0062] In a first aspect, the present invention provides a conductive adhesive, the conductive adhesive comprising a polymer, a polysaccharide, and a biomimetic additive;
[0063] When the conductive binder is used in a silicon-based negative electrode sheet, the biomimetic additive can undergo in-situ electrochemical polymerization during charge-discharge cycles, and synergistically form a functional solid electrolyte interface film on the surface of the silicon-based negative electrode with the polysaccharide material.
[0064] As a specific embodiment of the present invention, the biomimetic additive contains carbon-carbon double bonds and / or phenolic hydroxyl groups.
[0065] As a specific embodiment of the present invention, the biomimetic additive includes one or more of tannic acid, phytic acid, gallic acid, caffeic acid, dopamine, chlorogenic acid, ferulic acid, catechin, and catechol.
[0066] As a specific embodiment of the present invention, the biomimetic additive is caffeic acid and / or gallic acid.
[0067] As a specific embodiment of the present invention, the polysaccharide is a sulfur-containing polysaccharide and / or a carboxyl-containing polysaccharide.
[0068] As a specific embodiment of the present invention, the sulfur-containing polysaccharide includes carrageenan, heparin, chondroitin sulfate, fucosylated chondroitin sulfate, dermatan sulfate, and chemically modified sulfur-containing polysaccharides.
[0069] As a specific embodiment of the present invention, the chemically modified sulfur-containing polysaccharide refers to the natural sulfur-free polysaccharide that has been modified by sulfation to introduce a sulfate ester group.
[0070] As a specific embodiment of the present invention, the carboxyl-containing polysaccharide includes one or more of the following: sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, sodium alginate, sodium hyaluronate, xanthan gum, guar gum, locust bean gum, konjac glucomannan, gum arabic, pectin, tamarind gum, pullulan, carboxymethyl chitosan, and cross-linked starch.
[0071] Carboxylated polysaccharide molecules contain numerous carboxyl groups (-COOH) and hydroxyl groups. These polar groups can form dense intermolecular hydrogen bonds with the polymer backbone (such as polyacrylamide) in the binder. This hydrogen bonding causes the carboxylated polysaccharide and polymer chains to become entangled, forming a three-dimensional physical cross-linked network with a certain mechanical strength. This network, as a flexible backbone, provides basic adhesion and cohesion, helping to bind silicon particles together and initially buffering the approximately 300% volume expansion of silicon during charging and discharging, maintaining the structural integrity of the electrode. Furthermore, the carboxyl groups can form strong multi-point hydrogen bond anchoring with the natural oxide layer (Si-OH) on the surface of the silicon particles and the surface of the current collector. This "chemical anchoring" effect significantly enhances the bonding force between the active material layer and the current collector, preventing the silicon particles from detaching during repeated expansion and contraction, thus ensuring close electrical contact of the active layer during cycling.
[0072] More preferably, the sulfur-containing polysaccharide molecular chain has a unique sulfate ester group (-OSO3). - At the reduction potential during the first charge and discharge of the battery, these groups undergo electrochemical decomposition, giving rise to inorganic components with high ionic conductivity (such as Li₂S and SO₃). 2- These sulfur-rich components are in-situ incorporated into the solid electrolyte interphase (SEI) film on the surface of the silicon-based anode, giving the originally insulating SEI film excellent lithium-ion transport capabilities. The derived sulfur-rich SEI film exhibits extremely high lithium-ion conductivity, which synergistically works with the network formed by the in-situ polymerization of biomimetic additives (such as caffeic acid), constructing a robust and continuous fast ion transport channel at the electrode interface. This mechanism significantly reduces the charge transfer impedance at the interface, fundamentally solving the inherent bottleneck of slow ion transport kinetics at the silicon-based anode interface. During long-term cycling, the sulfur-containing polysaccharides continuously supply sulfur, ensuring a constant replenishment of beneficial inorganic components in the sulfur-rich SEI film. This avoids the problem of newly exposed interfaces continuously consuming electrolyte and active lithium due to lack of protection after the SEI film ruptures caused by the volume expansion and contraction of silicon particles. The sulfur-rich SEI film has better toughness and ductility, allowing it to undergo elastic deformation with the expansion and contraction of silicon particles without rupturing, thus maintaining long-term interface stability.
[0073] As a specific embodiment of the present invention, the polymer is obtained by free radical polymerization of monomers, wherein the monomers include one or more of acrylic acid, methacrylic acid, lithium acrylate, sodium acrylate, vinyl alcohol, ethylene glycol, acrylamide, and methacrylamide.
[0074] In a specific embodiment of the present invention, the polymer is polyacrylamide and / or polyacrylic acid.
[0075] Secondly, the present invention provides a method for preparing the conductive adhesive as described above, comprising the following steps:
[0076] (1) Add polysaccharide substances to the polymer solution and mix to obtain a polymer-polysaccharide composite solution;
[0077] (2) Add biomimetic additives to the polymer-polysaccharide composite solution and mix to obtain the conductive binder.
[0078] As a specific embodiment of the present invention, step S1 is included before step (1): dissolving the monomer in a solvent and carrying out a polymerization reaction under the action of an initiator to obtain a polymer solution.
[0079] As a specific embodiment of the present invention, the initiator includes one or more of potassium persulfate, sodium persulfate, ammonium persulfate, azobisisobutyronitrile, cerium sulfate, and cerium ammonium nitrate;
[0080] In step (1) of this invention, the mass ratio of monomer to initiator is (10-50):1, preferably 20:1. When the amount of initiator added is lower than the lower limit of this range (i.e., the mass ratio of monomer to initiator is greater than 50:1), the concentration of free radicals in the system is too low, the initiation efficiency is insufficient, resulting in a large number of monomers failing to participate in the polymerization reaction. Although the polymer molecular weight is high, the yield is low, and there are too many residual monomers in the solution. They are easy to volatilize or migrate during the subsequent coating and drying process, affecting the uniformity of the electrode. At the same time, the amount of initiator is too low, making the polymerization reaction rate too slow and difficult to reach the ideal degree of polymerization within a reasonable time. When the amount of initiator added is higher than the upper limit of this range (i.e., the mass ratio of monomer to initiator is less than 10:1), the concentration of free radicals in the system is too high, the initiation rate is too fast, and a large number of active centers grow simultaneously, resulting in concentrated exothermic polymerization reaction, which is prone to explosive polymerization, generating a large number of low molecular weight short-chain polymers with insufficient crosslinking network strength. In addition, excessive initiator remains in the binder, which may cause side reactions in the electrolyte during battery charging and discharging, damaging the electrochemical performance. When the monomer-to-initiator mass ratio is selected within the above range, the completeness of the polymerization reaction, the reasonable distribution of polymer molecular weight, and the minimization of the impact of residual initiator on battery performance can be considered. Specifically, this mass ratio can be 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, or 50:1, or any value within the range formed by any two of these values.
[0081] As a specific embodiment of the present invention, the solvent includes one or more of water, ethanol, ethylene glycol, n-propanol, isopropanol, and N-methyl-2-pyrrolidone.
[0082] As a specific embodiment of the present invention, in step (1), the polymerization temperature is 55-95℃, preferably 85℃. When the polymerization temperature is below 55℃, the thermal decomposition rate of the initiator (such as ammonium persulfate) is too low, and it cannot provide a sufficient concentration of free radicals within a reasonable time. The polymerization induction period is prolonged, the reaction rate is extremely slow, the monomer conversion rate is significantly low, and most monomers fail to polymerize to form long-chain structures, resulting in insufficient effective polymer content in the binder system. Consequently, a continuous network skeleton cannot be formed when compounded with polysaccharides. At the same time, the viscosity of the system increases at low temperatures, the diffusion of monomers in the reaction medium is hindered, the molecular weight distribution of the polymerization product is broadened, and the network uniformity is poor. When the polymerization temperature exceeds 95℃, the initiator decomposes too rapidly, generating a large number of free radicals in a short time. This leads to uncontrolled polymerization, prone to explosive polymerization and chain transfer reactions, and the formation of a large number of low-molecular-weight oligomers. Furthermore, the increased polymer chain movement at high temperatures facilitates cross-linking side reactions between molecules, resulting in poor product solubility and even gel formation. Simultaneously, temperatures approaching or exceeding the solvent boiling point (e.g., water boiling at 100℃ under normal pressure) cause instability in the reaction system, with significant solvent evaporation altering the reaction concentration and affecting polymerization consistency and reproducibility. Selecting a polymerization temperature within the aforementioned range balances the effective decomposition rate of the initiator, the stable and controllable polymerization reaction, and the excellent solubility of the polymer product. Specifically, the polymerization temperature can be 55℃, 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, 90℃, or 95℃, or any value within the range formed by any two of these values.
[0083] In a specific embodiment of the present invention, in step (2), the mass ratio of the polysaccharide to the monomer is (1~2):(1~4), preferably 1:2. When the polysaccharide ratio is lower than the lower limit of this range (i.e., the mass ratio of polysaccharide to monomer is less than 1:4), the polysaccharide content in the system is too low. On the one hand, it is impossible to form sufficient cross-linking nodes and hydrogen bond interaction sites in the polymer backbone, resulting in insufficient network cross-linking density and limited binding ability of silicon particles. On the other hand, the supply of polysaccharide precursors for co-derived SEI films is insufficient, making it difficult to form a stable SEI film rich in inorganic components on the silicon surface. The interface regulation effect is weak, and the improvement in battery rate performance and cycle life is limited. When the polysaccharide ratio exceeds the upper limit of this range (i.e., the polysaccharide-to-monomer mass ratio is greater than 2:1), the excessive polysaccharide component leads to several problems. Firstly, the high proportion of rigid segments increases the brittleness of the composite network, resulting in a lack of sufficient flexible segments to dissipate the mechanical stress generated by silicon expansion, making stress concentration and network breakage more likely. Secondly, excessive polysaccharide molecules tend to self-aggregate, forming polysaccharide-rich phase regions that undergo macroscopic phase separation from the polymer backbone, disrupting the homogeneity of the composite system. Furthermore, the excessively high polysaccharide content significantly increases the viscosity of the binder solution, hindering slurry coating. When the polysaccharide-to-monomer mass ratio is selected within the above range, a balance between the mechanical strength and toughness of the crosslinked network, a sufficient supply of SEI film precursors, and good processing rheology of the binder slurry can be achieved. Specifically, this mass ratio can be 1:4, 1:3, 1:2, 1:1, 3:2, or 2:1, or any value within the range formed by any two of these values.
[0084] As a specific embodiment of the present invention, in step (3), the amount of biomimetic additive added is 5-15% of the total mass of the solute, preferably 10%. When the amount of biomimetic additive added is less than 5%, there are insufficient active sites in the system that can participate in in-situ electrochemical polymerization. On the one hand, the dynamic crosslinking density is too low, and it is impossible to form a chemical crosslinking network of sufficient strength to assist the physical network in buffering the volume expansion of silicon. On the other hand, the phenolic hydroxyl anchoring sites provided by the biomimetic additive molecules on the surface of silicon particles are limited, the coating of the silicon surface is incomplete, and it is difficult to effectively inhibit the direct contact between silicon and electrolyte. The derivation regulation effect of the SEI film is weak, and the rate performance improvement effect is not good. When the biomimetic additive content exceeds 15%, excessive additives undergo over-crosslinking polymerization during electrochemical cycling, forming an overly dense crosslinked structure that blocks lithium-ion transport channels in the binder layer, resulting in a significant decrease in ionic conductivity. Simultaneously, a large number of phenolic hydroxyl groups may participate in irreversible side reactions in the electrochemical environment, continuously consuming active lithium, manifested as a significant decrease in both initial coulombic efficiency and cycle retention (as shown in Example 6, the initial coulombic efficiency drops to 78.3% at a 15% addition). When the biomimetic additive content is selected within the above range, it can balance the sufficient construction of the dynamic crosslinked network, the unobstructed lithium-ion transport channels, and the minimization of side reactions. Specifically, the addition amount can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, or 15%, or any value within the range formed by any two of these values. In one example, the addition amount was 10%, under which the binder exhibited optimal overall electrochemical performance.
[0085] Thirdly, the present invention provides a silicon-based negative electrode sheet, the silicon-based negative electrode sheet comprising a current collector and a negative electrode coating disposed on the surface of the current collector, the negative electrode coating comprising a silicon-based active material, a conductive agent and a conductive binder as described above or a conductive binder prepared by the preparation method described above.
[0086] In a specific embodiment of the present invention, the mass ratio of silicon-based active material, conductive agent, and conductive binder in the silicon-based negative electrode sheet is (5-7):(1-3):(1-3), preferably 6:2:2. When the binder content is lower than the lower limit of this range, the binder content is insufficient to form a continuous and complete network coating between silicon particles. A large number of silicon particles are exposed or only sparsely coated, resulting in insufficient cohesion between particles and a significant reduction in the mechanical strength of the electrode sheet. During the expansion and contraction process of charging and discharging, particle shedding and electrode sheet cracking are likely to occur. At the same time, a low binder content means that the proportion of active material in the unit area electrode sheet is too high. Although this is beneficial to improving the mass energy density, the conductive network support and volume buffer provided by the binder are seriously insufficient. When the binder percentage exceeds the upper limit of this range, although the stability of the electrode structure is improved, the excessive amount of binder, as a non-active component, occupies the electrode volume and mass. On the one hand, this dilutes the content of active material, leading to a decrease in battery energy density. On the other hand, binders are mostly electronically insulating polymers; excessive addition will coat the conductive agent and silicon particle surface, increasing the electron transport impedance and lithium-ion diffusion resistance inside the electrode, thus deteriorating rate performance. When the conductive agent percentage is below the lower limit of this range, the internal conductive network of the electrode is incomplete, electrons cannot be efficiently transported to the current collector, polarization increases, and the utilization rate of active material decreases. When the conductive agent percentage exceeds the upper limit of this range, excessive conductive agent will occupy a large number of gaps between silicon particles, hindering the liquid phase diffusion channels of lithium ions. Furthermore, the conductive agent itself does not have lithium storage capacity, and excessive addition will reduce the overall energy density. When the mass ratio of the three components is selected within the above range, the structural integrity of the electrode, the efficient construction of the electronic conductive network, the unobstructed ion transport channels, and the maximization of energy density can be balanced. Specifically, the mass ratio can be 5:2:3, 5:2.5:2.5, 5:3:2, 6:1:3, 6:2:2, 6:3:1, 7:1:2, 7:2:1, or 7:1.5:1.5, or any combination of any three of these values within a given range. In one example, the mass ratio is 6:2:2, under which the mechanical support, electronic conduction, and ion transport within the electrode achieve optimal synergy.
[0087] As a specific embodiment of the present invention, the silicon-based active material includes one or more of nano-silicon, micron-silicon, porous silicon, silicon-carbon composite, and silicon oxide;
[0088] As a specific embodiment of the present invention, the conductive agent includes one or more of conductive carbon black, carbon nanotubes, graphene, and Ketjen black.
[0089] Fourthly, the present invention provides a lithium-ion battery, the lithium-ion battery comprising the silicon-based negative electrode sheet as described above.
[0090] As a specific embodiment of the present invention, the lithium-ion battery has a discharge specific capacity of not less than 1200 mAh g at a 2C rate. -1 The lithium-ion battery retains no less than 50% of its capacity after 200 cycles at 1C rate.
[0091] The present application will be described in detail below with reference to the accompanying drawings and embodiments. However, the implementation and protection of the present invention are not limited thereto. The following embodiments are only some embodiments of the present application and are not intended to limit the present application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or in accordance with the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0092] Comparative Example 1
[0093] Carrageenan was dissolved in deionized water at 80 °C with stirring to prepare a 5% solution. After cooling, a lithium-ion battery negative electrode binder was obtained. A slurry was prepared by mixing nano-silicon powder, conductive carbon black, and binder in a ratio of 6:2:2, and this slurry was used to fabricate a lithium-ion battery negative electrode sheet. The electrochemical performance was then tested.
[0094] Comparative Example 2
[0095] Acrylic acid was dissolved in deionized water, and ammonium persulfate was added at a mass ratio of acrylic acid to ammonium persulfate of 20:1 to prepare a 5% solution. The solution was polymerized by stirring at 85 °C for 45 min, followed by cooling to obtain a lithium-ion battery negative electrode binder. A slurry was prepared by mixing nano-silicon powder, conductive carbon black, and binder in a ratio of 6:2:2, and this slurry was used to fabricate a lithium-ion battery negative electrode sheet. Electrochemical performance was then tested.
[0096] Comparative Example 3
[0097] Acrylamide was dissolved in deionized water, and ammonium persulfate was added at a mass ratio of 20:1 (acrylamide:ammonium persulfate) to prepare a 5% solution. The solution was polymerized by stirring at 85 °C for 45 min, followed by cooling to obtain a lithium-ion battery negative electrode binder. A slurry was prepared by mixing nano-silicon powder, conductive carbon black, and binder in a ratio of 6:2:2, and this slurry was used to fabricate a lithium-ion battery negative electrode sheet. Electrochemical performance was then tested.
[0098] The sample numbers, some physical properties, and electrochemical performance of Comparative Examples 1-3 are detailed in Table 1.
[0099] Table 1. Information and electrochemical performance of Comparative Examples 1-3
[0100] name adhesive Initial Coulomb efficiency (%) <![CDATA[2C rate performance (mAh g -1 )]]> 1C 200-cycle retention rate (%) Comparative Example 1 Carrageenan 71.5 0 22.1 Comparative Example 2 Polyacrylic acid 81.3 0 14.0 Comparative Example 3 Polyacrylamide 34.2 0 0
[0101] Comparative Examples 4-6
[0102] Acrylamide was dissolved in deionized water. Ammonium persulfate was added at a mass ratio of acrylamide to ammonium persulfate of 20:1, and polymerization was carried out at 85 °C for 45 min. Carrageenan was then added at different polyacrylamide-carrageenan mass ratios, controlling the total solute mass fraction to 5%, and the mixture was stirred at 80 °C for 20 min. After cooling, a lithium-ion battery negative electrode binder was obtained. A slurry was prepared using nano-silicon powder: conductive carbon black: binder in a ratio of 6:2:2, and this slurry was used to fabricate a lithium-ion battery negative electrode sheet. Electrochemical performance was then tested.
[0103] Sample numbers, preparation conditions, some physical properties and electrochemical performance are detailed in Table 2.
[0104] Table 2 Information and electrochemical performance of Comparative Examples 4-6
[0105] name Polyacrylamide: Carrageenan Initial Coulomb efficiency (%) <![CDATA[2C rate performance (mAh g -1 )]]> 1C 200-cycle retention rate (%) Comparative Example 4 1:2 83.4 0 33.0 Comparative Example 5 2:1 91.2 936.2 51.9 Comparative Example 6 4:1 91.0 521.7 47.4
[0106] As shown in Comparative Examples 4-6, among the single-component systems, pure polyacrylic acid exhibits the best performance due to its polar carboxyl group anchoring effect, followed by carrageenan, while pure polyacrylamide performs the worst. Examples 1-3 show that the electrochemical performance of the composite system initially increases and then decreases with the mass ratio of polyacrylamide to carrageenan, reaching its optimal value at 2:1. An appropriate ratio (2:1) can construct a robust three-dimensional cross-linked network, effectively buffering volume expansion and reducing side reactions; while excessive polysaccharides (1:2) lead to increased interfacial resistance and excessive rigidity, resulting in insufficient mechanical strength; excessive polyacrylamide (4:1) causes excessive network toughness and over-coating, severely hindering ion transport.
[0107] Examples 1-3
[0108] Acrylamide was dissolved in deionized water. Ammonium persulfate was added at a mass ratio of acrylamide to ammonium persulfate of 20:1, and polymerization was carried out at 85 °C for 45 min. Then, carrageenan was added at a mass ratio of polyacrylamide to carrageenan of 2:1, controlling the total solute mass fraction to 5%, and the mixture was stirred at 80 °C for 20 min. After cooling, caffeic acid, accounting for a certain proportion of the solute mass fraction, was added to obtain a lithium-ion battery negative electrode binder. A slurry was prepared by mixing nano-silicon powder, conductive carbon black, and binder in a ratio of 6:2:2, and this slurry was used to fabricate a lithium-ion battery negative electrode sheet. Electrochemical performance was then tested.
[0109] Sample numbers, preparation conditions, some physical properties and electrochemical performance are detailed in Table 3.
[0110] Table 3. Sample Information and Electrochemical Performance of Examples 1-3
[0111] name caffeic acid introduction amount (wt%) Initial Coulomb efficiency (%) <![CDATA[2C rate performance (mAh g -1 )]]> 1C 200-cycle retention rate (%) Example 1 5 91.9 1213.8 57.5 Example 2 10 92.8 1609.3 62.1 Example 3 15 78.3 872.5 51.2
[0112] As shown in Examples 1-3, the electrochemical performance of the silicon anode first increases and then decreases with the amount of caffeic acid introduced, reaching its optimal value at 10 wt%. An appropriate amount of caffeic acid can electrochemically and synergistically build fast ion channels with the polymer network and buffer volume expansion; however, excessive amounts lead to over-crosslinking, hindering ion transport and triggering more side reactions that consume active lithium, thus reducing electrochemical performance.
[0113] Comparative Example 7
[0114] Acrylamide was dissolved in deionized water. Ammonium persulfate was added at a mass ratio of acrylamide to ammonium persulfate of 20:1, and the mixture was stirred at 85 °C for 45 min to polymerize. Then, sodium carboxymethyl cellulose was added at a mass ratio of polyacrylamide to sodium carboxymethyl cellulose of 2:1, controlling the total solute mass fraction to 5%, and the mixture was stirred at 80 °C for 20 min. After cooling, a lithium-ion battery negative electrode binder was obtained. A slurry was prepared by mixing nano-silicon powder, conductive carbon black, and binder in a ratio of 6:2:2, and this slurry was used to fabricate a lithium-ion battery negative electrode sheet. The electrochemical performance was then tested.
[0115] Example 4
[0116] Acrylamide was dissolved in deionized water. Ammonium persulfate was added at a mass ratio of acrylamide to ammonium persulfate of 20:1, and polymerization was carried out at 85 °C for 45 min. Then, sodium carboxymethyl cellulose was added at a mass ratio of polyacrylamide to sodium carboxymethyl cellulose of 2:1, controlling the total solute mass fraction to 5%, and the mixture was stirred at 80 °C for 20 min. After cooling, 10% caffeic acid was added to obtain a lithium-ion battery negative electrode binder. A slurry was prepared by mixing nano-silicon powder, conductive carbon black, and binder in a ratio of 6:2:2, and this slurry was used to fabricate a lithium-ion battery negative electrode sheet. Electrochemical performance was then tested.
[0117] Sample numbers, some physical properties and electrochemical performance details are shown in Table 4.
[0118] Table 4. Sample information and electrochemical performance of Comparative Example 7 and Example 4
[0119] name Adhesive formulation Initial Coulomb efficiency (%) <![CDATA[2C rate performance (mAh g -1 )]]> 1C 200-cycle retention rate (%) Comparative Example 7 Polyacrylamide: Sodium carboxymethyl cellulose 91.2 884.9 43.6 Example 4 Polyacrylamide: Sodium carboxymethyl cellulose: Caffeic acid 92.3 1205.1 50.9
[0120] As shown in Comparative Example 7 and Example 4, the introduction of caffeic acid also significantly improved the rate capacity and cycle life of the polyacrylamide-sodium carboxymethyl cellulose system, proving the universality of the in-situ polymerization strategy. However, the overall performance of the sodium carboxymethyl cellulose system is still significantly inferior to that of the carrageenan system with the same proportions, mainly because sodium carboxymethyl cellulose can only provide basic network support and cannot improve the SEI film of the electrode.
[0121] Comparative Example 8
[0122] Acrylic acid was dissolved in deionized water. Ammonium persulfate was added at a mass ratio of acrylamide to ammonium persulfate of 20:1, and polymerization was carried out at 85 °C for 45 min. Then, carrageenan was added at a mass ratio of polyacrylic acid to carrageenan of 2:1, controlling the total solute mass fraction to 5%, and the mixture was stirred at 80 °C for 20 min. After cooling, a lithium-ion battery negative electrode binder was obtained. A slurry was prepared by mixing nano-silicon powder, conductive carbon black, and binder in a ratio of 6:2:2, and this slurry was used to fabricate a lithium-ion battery negative electrode sheet. Electrochemical performance was then tested.
[0123] Example 5
[0124] Acrylic acid was dissolved in deionized water, and ammonium persulfate was added at a mass ratio of acrylic acid to ammonium persulfate of 20:1. Polymerization was carried out at 85 °C for 45 min with stirring. Then, carrageenan was added at a mass ratio of polyacrylic acid to carrageenan of 2:1, controlling the total solute mass fraction to 5%, and the mixture was stirred at 80 °C for 20 min. After cooling, 10% caffeic acid was added to obtain the lithium-ion battery negative electrode binder. A slurry was prepared by mixing nano-silicon powder, conductive carbon black, and binder in a ratio of 6:2:2, and this slurry was used to fabricate a lithium-ion battery negative electrode sheet. Electrochemical performance was then tested.
[0125] Sample numbers, some physical properties and electrochemical performance details are shown in Table 5.
[0126] Table 5. Detailed information, physical properties, and electrochemical performance of Comparative Example 8 and Example 5 samples.
[0127] name Adhesive formulation Initial Coulomb efficiency (%) <![CDATA[2C rate performance (mAh g -1 )]]> 1C 200-cycle retention rate (%) Comparative Example 8 Polyacrylic acid: carrageenan 90.1 652.0 12.8 Example 5 Polyacrylic acid: carrageenan: caffeic acid 92.6 723.2 20.4
[0128] As shown in Comparative Example 8 and Example 2, the overall performance of the polyacrylic acid-carrageenan composite system is significantly inferior to that of the polyacrylamide system with the same proportions. This is mainly because the strong acidity of polyacrylic acid catalyzes the hydrolytic breakage of the carrageenan backbone upon heating. This irreversible acidic hydrolysis severely damages the polymer backbone of the polysaccharide, leading to a significant decrease in the mechanical strength of the crosslinked network. In contrast, neutral polyacrylamide better preserves the long-chain backbone of carrageenan.
[0129] Example 6
[0130] Acrylamide was dissolved in deionized water. Ammonium persulfate was added at a mass ratio of acrylamide to ammonium persulfate of 20:1, and polymerization was carried out at 85 °C for 45 min. Then, carrageenan was added at a mass ratio of polyacrylamide to carrageenan of 2:1, controlling the total solute mass fraction to 5%, and the mixture was stirred at 80 °C for 20 min. After cooling, gallic acid with a solute mass fraction of 10% was added to obtain the lithium-ion battery negative electrode binder. A slurry was prepared by mixing nano-silicon powder, conductive carbon black, and binder in a ratio of 6:2:2, and this slurry was used to fabricate a lithium-ion battery negative electrode sheet. Electrochemical performance was then tested.
[0131] Sample numbers, some physical properties and electrochemical performance details are shown in Table 6.
[0132] Table 6 Physical properties and electrochemical performance of the sample from Example 6
[0133] name Adhesive formulation Initial Coulomb efficiency (%) <![CDATA[2C rate performance (mAh g -1 )]]> 1C 200-cycle retention rate (%) Example 6 Polyacrylamide: Carrageenan: Gallic acid 90.6 1319.5 50.7
[0134] As can be seen from Examples 6 and 2, the overall performance of the gallic acid system is significantly inferior to that of caffeic acid at the same concentration. This is because gallic acid molecules lack polymerizable double bonds and cannot undergo electrochemical in-situ polymerization to build a dynamic network like caffeic acid. Therefore, they can only provide static adhesion and are unable to provide long-term buffering for the huge volume expansion of the silicon anode.
[0135] Examples 7 and 8
[0136] Acrylamide was dissolved in deionized water. Ammonium persulfate was added at a mass ratio of acrylamide to ammonium persulfate of 20:1, and the mixture was stirred at 85 °C for a period of time to polymerize. Then, carrageenan was added at a mass ratio of polyacrylamide to carrageenan of 2:1, controlling the total solute mass fraction to 5%, and the mixture was stirred at 80 °C for 20 min. After cooling, 10% caffeic acid was added to obtain a lithium-ion battery negative electrode binder. A slurry was prepared by mixing nano-silicon powder, conductive carbon black, and binder in a ratio of 6:2:2, and this slurry was used to fabricate a lithium-ion battery negative electrode sheet. The electrochemical performance was then tested.
[0137] Sample numbers, some physical properties and electrochemical performance details are shown in Table 7.
[0138] Table 7. Detailed information, physical properties, and electrochemical performance of samples from Examples 7 and 8.
[0139] name Aggregation time (min) Initial Coulomb efficiency (%) <![CDATA[2C rate performance (mAh g -1 )]]> 1C 200-cycle retention rate (%) Example 7 10 80.8 0 6.8 Example 8 80 82.6 441.7 11.5
[0140] As demonstrated in Examples 7, 8, and Example 2, the electrochemical performance of the electrode decreases when the temperature or time of the first-step polymerization deviates from the optimal conditions (85 °C, 45 min). Too low a polymerization temperature or too short a time leads to low monomer conversion and short polymer chains, resulting in insufficient network mechanical strength. Conversely, too high a temperature or too long a time can cause excessive reaction or over-crosslinking, making the polymer network overly brittle, hindering ion transport and failing to provide long-term buffering against the severe volume expansion of the silicon anode.
[0141] Examples 9 and 10
[0142] Acrylamide was dissolved in deionized water. Ammonium persulfate was added at a mass ratio of acrylamide to ammonium persulfate of 20:1, and the mixture was stirred at 85 °C for 45 min to polymerize. Then, carrageenan was added at a mass ratio of polyacrylamide to carrageenan of 2:1, controlling the total solute mass fraction to 5%, and stirred at a certain temperature for 20 min. After cooling, 10% caffeic acid was added to obtain a lithium-ion battery negative electrode binder. A slurry was prepared by mixing nano-silicon powder, conductive carbon black, and binder in a ratio of 6:2:2, and this slurry was used to fabricate a lithium-ion battery negative electrode sheet. Electrochemical performance was then tested.
[0143] Sample numbers, some physical properties and electrochemical performance details are shown in Table 8.
[0144] Table 8. Detailed information, physical properties, and electrochemical performance of samples from Examples 9 and 10.
[0145] name Second step reaction temperature (°C) Initial Coulomb efficiency (%) <![CDATA[2C rate performance (mAh g -1 )]]> 1C 200-cycle retention rate (%) Example 9 60 88.4 859.2 41.5 Example 10 90 89.6 931.4 48.5
[0146] Examples 11 and 12
[0147] Acrylamide was dissolved in deionized water. Ammonium persulfate was added at a mass ratio of acrylamide to ammonium persulfate of 20:1, and polymerization was carried out at 85 °C for 45 min. Then, carrageenan was added at a mass ratio of polyacrylamide to carrageenan of 2:1, controlling the total solute mass fraction to 5%, and the mixture was stirred at 80 °C for a period of time. After cooling, 10% caffeic acid was added to obtain the lithium-ion battery negative electrode binder. A slurry was prepared by mixing nano-silicon powder, conductive carbon black, and binder in a ratio of 6:2:2, and this slurry was used to fabricate a lithium-ion battery negative electrode sheet. Electrochemical performance was then tested.
[0148] Sample numbers, some physical properties and electrochemical performance details are shown in Table 9.
[0149] Table 9. Detailed information, physical properties, and electrochemical performance of samples from Examples 11 and 12.
[0150] name Second step reaction time (min) Initial Coulomb efficiency (%) <![CDATA[2C rate performance (mAh g -1 )]]> 1C 200-cycle retention rate (%) Example 11 3 74.7 766.5 26.8 Example 12 60 91.0 914.2 43.3
[0151] As shown in Examples 11, 12, and Example 2, the overall performance of the electrode decreased when the reaction temperature or stirring time in the second step after adding carrageenan deviated from the optimal conditions. Too low a temperature or too short a time resulted in incomplete dissolution and uneven dispersion of the carrageenan, making it difficult to fully entangle with the polyacrylamide generated in the first step to construct a uniform composite network. Too high a temperature easily caused thermal degradation and breakage of the carrageenan polysaccharide chains, while too long a time could lead to the polymer chains being damaged or excessively cross-linked under continuous shear force. Ultimately, neither of these conditions could form a strong and resilient three-dimensional network to effectively buffer the volume expansion of the silicon anode.
[0152] Examples 13 and 14
[0153] Acrylamide was dissolved in deionized water, and ammonium persulfate was added at a specific monomer-to-initiator mass ratio. Polymerization was carried out at 85 °C for 45 min with stirring. Then, carrageenan was added at a polyacrylamide:carrageenan mass ratio of 2:1, controlling the total solute mass fraction to 5%, and the mixture was stirred at 80 °C for 20 min. After cooling, 10% caffeic acid was added to obtain a lithium-ion battery negative electrode binder. A slurry was prepared using nano-silicon powder:conductive carbon black:binder in a ratio of 6:2:2 and fabricated into a lithium-ion battery negative electrode sheet. Electrochemical performance was then tested.
[0154] Sample numbers, some physical properties and electrochemical performance details are shown in Table 10.
[0155] Table 10 Detailed information, physical properties, and electrochemical performance of samples from Examples 13 and 14
[0156] name Monomer: Initiator Initial Coulomb efficiency (%) <![CDATA[2C rate performance (mAh g -1 )]]> 1C 200-cycle retention rate (%) Example 13 10:1 83.9 0 0 Example 14 50:1 71.6 237.1 8.9
[0157] Example 15
[0158] Acrylamide was dissolved in deionized water, and ceric ammonium nitrate was added at a mass ratio of acrylamide to ceric ammonium nitrate of 20:1. Polymerization was carried out at 85 °C for 45 min. Then, carrageenan was added at a mass ratio of polyacrylamide to carrageenan of 2:1, controlling the total solute mass fraction to 5%, and the mixture was stirred at 80 °C for 20 min. After cooling, 10% caffeic acid was added to obtain the lithium-ion battery negative electrode binder. A slurry was prepared by mixing nano-silicon powder, conductive carbon black, and binder in a ratio of 6:2:2, and this slurry was used to fabricate a lithium-ion battery negative electrode sheet. Electrochemical performance was then tested.
[0159] Sample numbers, some physical properties and electrochemical performance details are shown in Table 11.
[0160] Table 11 Detailed information, physical properties and electrochemical performance of sample 15 in Example 15
[0161] name Initiator Initial Coulomb efficiency (%) <![CDATA[2C rate performance (mAh g -1 )]]> 1C 200-cycle retention rate (%) Example 15 Cerium ammonium nitrate 83.9 0 6.8
[0162] As shown in Examples 13-15, changing the amount of initiator added or replacing the initiator with cerium ammonium nitrate resulted in a decline in the electrochemical performance of the electrode. Insufficient initiator led to insufficient free radical concentration, low monomer conversion rate, and incomplete polymerization; while excessive initiator caused the polymerization reaction to be too fast, resulting in a lower molecular weight of the polymer. Neither method could construct a high-strength cross-linked network. Furthermore, the initiation kinetics of cerium ammonium nitrate differed from those of ammonium persulfate, making it difficult to form an ideal three-dimensional synergistic network in the existing system, ultimately leading to a deterioration in rate performance and cycling performance.
[0163] Figure 1The infrared spectrum of the prepared adhesive is shown. Comparative Example 1 (pure carrageenan) exhibits characteristic peaks of sulfate groups (~1220-1260 cm⁻¹). -1 and ~800-850 cm -1 Comparative Example 3 (pure polyacrylamide) exhibited an amide I band (~1650 cm⁻¹). -1 ) and amide II band (~1550 cm) -1 In contrast, in Comparative Example 5 (polyacrylamide-carrageenan composite), the amide I band showed a significant red shift and broadened peak shape, indicating that intermolecular hydrogen bonds were formed between polyacrylamide and carrageenan; in Example 2 (further introduction of caffeic acid), the OH / NH stretching vibration region (~3400 cm⁻¹) was observed. -1 The broadening of the spectrum of caffeic acid is more significant than that of comparative example 5, and the characteristic peak of the phenolic hydroxyl group is enhanced, which confirms that the phenolic hydroxyl group of caffeic acid participates in the construction of the cross-linking network as an additional hydrogen bond donor. At the same time, the characteristic peak of the sulfate ester of carrageenan remains stable in each composite system, proving that its sulfur-containing skeleton is not destroyed during the composite process. This spectroscopic evidence confirms at the molecular level that the three components form a uniform network through multiple hydrogen bonds, which lays the structural foundation for the construction of a dynamic dual-effect network in subsequent electrochemical cycles.
[0164] Figure 2 The nanoindentation test curves of the binders prepared in Comparative Examples 5, 7 and Example 2 are shown. Comparative Example 7 (polyacrylamide-sodium carboxymethyl cellulose) has a lower loading curve slope and the largest residual displacement, reflecting its low hardness and elastic modulus and insufficient resistance to plastic deformation. Comparative Example 5 (polyacrylamide-carrageenan) has a higher loading curve slope and an increased elastic recovery ratio, which is attributed to the stronger mechanical support provided by the double helix structure of carrageenan. Example 2 (polyacrylamide-carrageenan-caffeic acid) has the highest loading curve slope, the smallest maximum indentation depth, the steepest initial segment of the unloading curve, and extremely small residual displacement, exhibiting the optimal synergistic mechanical properties of "high strength and high toughness". This is due to the high energy dissipation capacity of the additional cross-linking nodes and multiple hydrogen bond networks provided by caffeic acid, which provides mechanical protection for long-term buffering of silicon volume expansion.
[0165] Figure 3The 180° peel strength curves of the binders prepared in Comparative Example 5 and Example 2 corresponding to the silicon anode sheets are shown. Comparative Example 5 (polyacrylamide-carrageenan) exhibits a higher average peel strength and smaller curve fluctuations, proving that the amide groups and hydroxyl groups form effective multi-point hydrogen bond anchoring with the Si-OH on the silicon surface. The peel strength of Example 2 (polyacrylamide-carrageenan-caffeic acid) is further improved and the peel force decay is more gradual. This is because the catechol structure of caffeic acid molecules can form bidentate hydrogen bonds and even chemical chelation with the silicon surface. Its "multi-claw anchoring" mechanism makes the interfacial bonding force much higher than that of simple single-point hydrogen bonding. At the same time, caffeic acid enhances the cohesive strength of the binder layer. These results prove that the binder of the present invention has a super strong anchoring ability for silicon and current collector surfaces, ensuring that the active material layer maintains close electrical contact with the current collector during repeated expansion and contraction.
[0166] Figure 4 The first-week constant current charge-discharge curves of Comparative Examples 3, 5, 7 and Example 2 are shown. Comparative Example 3 (pure polyacrylamide) lacks effective anchoring groups and volume buffering capacity, resulting in a significant long plateau in the first-week charging curve and extremely large irreversible capacity, with an initial coulombic efficiency of only 34.2%. Comparative Example 5 (polyacrylamide-carrageenan) shows a significant reduction in irreversible capacity due to carrageenan's participation in SEI film derivation, achieving an initial coulombic efficiency of 91.2%. Comparative Example 7 (polyacrylamide-sodium carboxymethyl cellulose) further increases to 92.3%, but sodium carboxymethyl cellulose does not contain sulfur and cannot derive the optimal SEI component. Example 2 (polyacrylamide-carrageenan-caffeic acid) reaches the highest at 92.8%. Its core mechanism is that caffeic acid undergoes in-situ polymerization during the first-week charging to form a protective layer, while the sulfate groups of carrageenan decompose at the reduction potential to derive sulfur-rich SEI components such as Li2S. The two work synergistically to achieve complete coating of the silicon surface and suppress side reactions to the greatest extent, thus achieving excellent first-week coulombic efficiency.
[0167] Figure 5 The graph shows the rate performance of the adhesives prepared in Comparative Examples 5, 7, and Example 2 at different current densities. Comparative Example 7 (polyacrylamide-sodium carboxymethyl cellulose) has a rate performance of approximately 2500 mAh g at 0.1C. -1 However, at 2C, it drops sharply to 936.2 mAh g. -1 This is mainly because the basic system lacks both an active sulfur source capable of generating a highly conductive SEI film and a fast ion channel for dynamic cross-linking. Conventional CMC polysaccharide networks suffer severe obstacles to interfacial lithium-ion transport at high rates. Comparative Example 5 (polyacrylamide-carrageenan), although not yet in-situ polymerized with biomimetic additives, utilizes the unique sulfate groups of carrageenan to generate a sulfur-rich SEI component with high ionic conductivity in an electrochemical environment. This improves the interfacial charge transport kinetics to some extent, increasing the 2C to 1158.4 mAh g⁻¹.-1 Example 2 (polyacrylamide-carrageenan-caffeic acid) showed optimal performance at all rate ranges, with the most significant advantage at high rate ranges—a 2C concentration of up to 1609.3 mAh g. -1 The mechanism lies in the fact that the inorganic components such as Li2S in the sulfur-rich SEI film derived from carrageenan have extremely high lithium-ion conductivity, which forms a "fast ion channel" synergistic effect with the in-situ polymerization network of caffeic acid, fundamentally solving the inherent bottleneck of slow ion transport dynamics at the interface of silicon-based anodes.
[0168] Figure 6 The graph shows the long-cycle performance of Example 2 at a current density of 1C. After the first activation cycle, the coulombic efficiency quickly stabilizes above 99.5%, and the capacity retention reaches 62.1% after 200 cycles. The decay curve is smooth and there are no sudden rapid decay characteristics. This excellent performance is due to three synergistic mechanisms: First, caffeic acid undergoes in-situ polymerization in the first cycle, further strengthening the binder network and enhancing the adhesion between silicon particles and silicon and current collector through the biomimetic strong coordination of catechol, maintaining the structural stability of the electrode during cycling. Second, carrageenan continuously supplies sulfur, constantly replenishing the inorganic components in the sulfur-rich SEI film and avoiding the cumulative increase of interfacial impedance. Third, the non-covalent bonds in the multiple hydrogen bond network preferentially break as "sacrificial bonds" to dissipate stress while the covalent skeleton remains intact. This biomimetic energy dissipation mechanism ensures that the network maintains structural integrity throughout long cycles. The synergy of these three factors breaks the cycle decay mode of traditional static networks that leads to sudden failure due to stress accumulation.
[0169] Figure 7 The images show SEM comparisons of the electrode cross-sections before and after cycling in Comparative Examples 5, 7, and Example 2. Before cycling, the cross-sections of each example were flat and dense, with a clear and tight interface between the active layer and the copper foil. However, significant differences were observed after cycling: the thickness increase in Comparative Example 5 (polyacrylamide-carrageenan) was reduced, but localized loose areas still existed inside; the thickness in Comparative Example 7 (polyacrylamide-sodium carboxymethyl cellulose) increased significantly, and slight separation appeared at the interface, with microcracks visible inside, indicating limited buffering capacity of the static network; while the thickness increase in Example 2 (polyacrylamide-carrageenan-caffeic acid) was small after cycling, with no separation at the interface, and the active layer remained dense without any cracks. This is because the strong anchoring of catechol firmly binds the silicon particles, the dynamic cross-linking network absorbs volume changes through elastic deformation without breaking, and the sulfur-rich SEI film restricts silicon expansion within the shell. These three factors work together to suppress interparticle compression and misalignment, resulting in an electrode thickness expansion rate far lower than in other examples.
[0170] Figure 8The images show SEM comparisons of the electrode surfaces before and after bonding in Comparative Examples 5, 7, and Example 2. Before bonding, the surfaces of all examples were smooth and uniform. However, after bonding, Comparative Example 7 (polyacrylamide-sodium carboxymethyl cellulose) showed numerous through-cracks, exposing silicon particles in some areas, indicating fatigue failure of the bonding agent network. Comparative Example 5 (polyacrylamide-carrageenan) showed a reduced crack density but still exhibited obvious linear cracks. Example 2 (polyacrylamide-carrageenan-caffeic acid) remained smooth and dense after bonding, with virtually no observable cracks. This is because the dynamic cross-linking network repairs surface micro-damage in its early stages, preventing crack propagation. The sulfur-rich SEI film possesses excellent toughness and ductility, allowing for elastic deformation with the expansion and contraction of silicon particles without rupture. Simultaneously, internal expansion of the electrode was effectively suppressed, resulting in tensile stress transmitted to the surface far below the network fracture threshold. This result is consistent with... Figure 7 The evidence corroborates each other, confirming from both surface and cross-sectional dimensions that the binder network of this invention can still maintain the integrity of the electrode structure after 200 cycles, which is of breakthrough significance in the field of pure silicon anodes.
[0171] The present invention has been described in detail above, with the aim of enabling those skilled in the art to understand and implement the invention. However, this description should not be construed as limiting the scope of protection of the invention. All equivalent changes or modifications made in accordance with the spirit and essence of the invention should be included within the scope of protection of the invention.
[0172] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A conductive adhesive, characterized in that, The conductive binder includes polymers, polysaccharides, and biomimetic additives; When the conductive binder is used in a silicon-based negative electrode sheet, the biomimetic additive can undergo in-situ electrochemical polymerization during charge-discharge cycles, and synergistically form a functional solid electrolyte interface film on the surface of the silicon-based negative electrode with the polysaccharide material.
2. The conductive adhesive according to claim 1, characterized in that, The biomimetic additive contains carbon-carbon double bonds and / or phenolic hydroxyl groups; Preferably, the biomimetic additive includes one or more of tannic acid, phytic acid, gallic acid, caffeic acid, dopamine, chlorogenic acid, ferulic acid, catechin, and catechol; More preferably, the biomimetic additive is caffeic acid and / or gallic acid.
3. The conductive adhesive according to claim 1, characterized in that, The polysaccharide is a sulfur-containing polysaccharide and / or a carboxyl-containing polysaccharide; Preferably, the sulfur-containing polysaccharide includes carrageenan, heparin, chondroitin sulfate, fucoidan-modified chondroitin sulfate, dermatan sulfate, and chemically modified sulfur-containing polysaccharides. More preferably, the chemically modified sulfur-containing polysaccharide refers to the natural sulfur-free polysaccharide that has been sulfated to introduce a sulfate ester group; And / or, the carboxyl-containing polysaccharide includes one or more of the following: sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, sodium alginate, sodium hyaluronate, xanthan gum, guar gum, locust bean gum, konjac glucomannan, gum arabic, pectin, tamarind gum, pullulan, carboxymethyl chitosan, and cross-linked starch.
4. The conductive adhesive according to any one of claims 1 to 3, characterized in that, The polymer is obtained by free radical polymerization of monomers, wherein the monomers include one or more of acrylic acid, methacrylic acid, lithium acrylate, sodium acrylate, vinyl alcohol, ethylene glycol, acrylamide, and methacrylamide. Preferably, the polymer is polyacrylamide and / or polyacrylic acid.
5. A method for preparing the conductive adhesive as described in any one of claims 1 to 4, characterized in that, Includes the following steps: (1) Add polysaccharide substances to the polymer solution and mix to obtain polymer-polysaccharide composite solution; (2) Add biomimetic additives to the polymer-polysaccharide composite solution and mix to obtain the conductive binder.
6. The preparation method according to claim 5, characterized in that, Step (1) is preceded by step S1: dissolving the monomer in a solvent and carrying out a polymerization reaction under the action of an initiator to obtain a polymer solution; Preferably, the initiator includes one or more of potassium persulfate, sodium persulfate, ammonium persulfate, azobisisobutyronitrile, cerium sulfate, and cerium ammonium nitrate; Preferably, the mass ratio of the monomer to the initiator is (10-50):1; Preferably, the polymerization reaction temperature is 55-95°C; the polymerization reaction time is 10-120 min. Preferably, the solvent includes one or more of water, ethanol, ethylene glycol, n-propanol, isopropanol, and N-methyl-2-pyrrolidone.
7. The preparation method according to claim 6, characterized in that, In step (1), the mass ratio of the polysaccharide to the monomer is 1:4 to 2:1; And / or, in step (2), the amount of the biomimetic additive added is 5-15% of the total mass of the binder.
8. A silicon-based negative electrode sheet, characterized in that, The silicon-based negative electrode sheet includes a current collector and a negative electrode coating disposed on the surface of the current collector. The negative electrode coating includes a silicon-based active material, a conductive agent, and a conductive binder as described in any one of claims 1 to 4 or a conductive binder prepared by any one of claims 5 to 7.
9. The silicon-based negative electrode sheet according to claim 8, characterized in that, The mass ratio of the silicon-based active material, the conductive agent and the conductive binder is (5-7):(1-3):(1-3); And / or, the silicon-based active material includes one or more of nano-silicon, micron-silicon, porous silicon, silicon-carbon composite, and silicon oxide; And / or, the conductive agent includes one or more of conductive carbon black, carbon nanotubes, graphene, and Ketjen black.
10. A lithium-ion battery, characterized in that, The lithium-ion battery includes the silicon-based negative electrode sheet as described in claim 8 or 9; The lithium-ion battery has a discharge specific capacity of not less than 1200 mAh g at a 2C rate. -1 ; And / or, the capacity retention rate of the lithium-ion battery after 200 cycles at 1C rate is not less than 50%.
Citation Information
Patent Citations
Multifunctional composite binder for silicon-carbon anode of lithium ion battery and preparation method and application thereof
CN120829740B
